ARDUINO-BASED ROBOT WITH RFID UTILIZATION AS AN EDUCATIONAL MEDIA FOR INDONESIAN TRADITIONAL FOLK SONG AND PANCASILA - Hidayatullah, Bagus Arif; Hadary, Ferry; Marindani, Elang Derdian (Faculty of Engineering, Universitas Tanjungpura, 2024)
Nowadays, traditional folk songs and Pancasila are being forgotten among the younger generation. This is primarily due to lack of initiatives reintroduce of it. Addressing this issue, Arduino-based Robot with RFID Utilization was developed as educational medium for traditional folk songs and Pancasila by playing traditional folk songs and Pancasila through RFID cards, which feature descriptions of traditional folk songs and Pancasila on the front of the cards, a unique educational experience is created. This is further enhanced by combining it with a board game where participants guess the titles of traditional folk songs or Pancasila. This robot functions by detecting and following objects in front of it using ultrasonic sensor. Equipped with servo motor for movement and capable of playing traditional folk songs and Pancasila through an RFID card, which is read by RFID module (RC522) in conjunction with DFPlayer Mini to produce sound from MP3 files. From the results of the RFID card reading test, which involved 30 cards, average reading speed was 14.888 seconds, with reading distance ranging from 0 to 3 cm. The object detection range was between 0 and 6 cm, with average travel speed of 0.481 cm/second. The conclusion drawn from this research is that designed robot performs well, as it can approach objects in front of it and read all compatible RFID cards to play collection of 25 traditional folk songs and the 5 principles of Pancasila in the form of MP3 files.